SYSTEM FOR DYNAMICALLY CHARGING A COKE OVEN - CHOI, CHUN WAI; BALL, MARK ANTHONY; QUANCI, JOHN FRANCIS (2021)
Systems and methods of dynamically charging coal in coke ovens related to the operation and output of coke plants including methods of automatically charging a coke oven using a charging ram in communication with a control system to increase the coke output and coke quality from coke plants. In some embodiments, the control system is capable of moving the charging ram in a horizontal first direction, a horizontal second direction and a vertical third direction while charging coal into the oven. In some embodiments, the coal charging system also includes a scanning system configured to scan an oven floor to generate an oven floor profile and/or oven capacity. The scanning system used in combination with the control system allows for dynamic leveling of the charging ram throughout the charging process. In some embodiments, the charging ram includes stiffener plates and support members to increase the mechanical strength of the charging ram and decrease the sag of the charging ram at a distal end.